EFFECT OF PUMPKIN (CUCURBITA PEPO L.) AND MARIGOLD (TAGETES PATULA L.) EXTRACTS ON HIPPOCAMPAL MITOCHONDRIA FUNCTIONAL ACTIVITY WITHIN CONDITIONS OF EXPERIMENTAL ACUTE BRAIN HYPOMETABOLISM - A. V. Voronkov; D. I. Pozdnyakov; S. L. Adzhiakhmetova; N. M. Chervonnaya; K. A. Miroshnichenko; A. V. Sosnovskaya; E. I. Chereshkova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
The aim of the study is to evaluate the effect of pumpkin (Cucurbita pepo L.) and marigold extracts (Tagetes patula L.) on the hippocampal mitochondria functional activity within the conditions of experimental acute brain hypometabolism.Materials and methods. The work was performed on 50 male Wistar rats, which reproduced an acute brain hypometabolic state by administration of a 3M sodium azide solution in hippocampus (n = 40 and n = 10 - a group of sham-operated animals). The test extracts and the reference drug - EGb 761 - were prophylactically administered at the dose of 100 mg/kg per os for 10 days. 24 hours after the last administration, sodium azide was injected, the brain was taken, the hippocampus was isolated to obtain a supernatant and determine the parameters of mitochondrial respiration, the intensity of anaerobic processes, the concentration of the apoptosis-inducing factor, endonuclease G, and β-amyloid.Results. The carried out study established that the prophylactic administration of pumpkin and marigold extracts contributed to the restoration of a mitochondrial function and a decrease in the intensity of anaerobic processes. In the group of the rats treated with pumpkin and marigold extracts, an increase of ATP concentration in the hippocampal supernatant by 65.7% (p<0.002) was observed; it was 66.2% (p><0.002) relative to the animals deprived of pharmacological support. ,When the rats were treated with pumpkin and marigold extracts, a decrease in the concentration of apoptosis-inducing factor (by 33% (p><0.002) and 38.3% (p><0.002), respectively) and endonuclease G (by 3.6 times (p><0.002) and 4.4 times (p><0.002), respectively) was also noted. The administration of pumpkin and marigold extracts reduced the amyloid β-peptide concentration in the rats' hippocampus by 54.4% (p><0.0002) and 54.4% (p><0.0002), respectively. The test-extracts had an equivalent therapeutic efficacy with the reference drug. Conclusion On the basis of the obtained data, it is possible to suggest the prospect of a further study of pumpkin and marigold extracts as the drugs of a targeted correction of cerebral hypometabolism. Keywords: plant extracts, hypometabolism, hippocampus, mitochondria >< 0.002) was observed; it was 66.2% (p<0.002) relative to the animals deprived of pharmacological support. ,When the rats were treated with pumpkin and marigold extracts, a decrease in the concentration of apoptosis-inducing factor (by 33% (p><0.002) and 38.3% (p><0.002), respectively) and endonuclease G (by 3.6 times (p><0.002) and 4.4 times (p><0.002), respectively) was also noted. The adm>< 0.002) relative to the animals deprived of pharmacological support. ,When the rats were treated with pumpkin and marigold extracts, a decrease in the concentration of apoptosis-inducing factor (by 33% (p<0.002) and 38.3% (p><0.002), respectively) and endonuclease G (by 3.6 times (p><0.002) and 4.4 times (p><0.002), respectively) was also noted. The administration of pumpki>< 0.002) and 38.3% (p<0.002), respectively) and endonuclease G (by 3.6 times (p><0.002) and 4.4 times (p><0.002), respectively) was also noted. The administration of pumpkin and marigold extracts reduced the amyloid β-peptide concentration in the rats' hippocampus by 54.4% (p><0.0002) and 54.4% (p><0.0002), respectively. The test-extracts had an equivalent therapeutic efficacy with >< 0.002), respectively) and endonuclease G (by 3.6 times (p<0.002) and 4.4 times (p><0.002), respectively) was also noted. The administration of pumpkin and marigold extracts reduced the amyloid β-peptide concentration in the rats' hippocampus by 54.4% (p><0.0002< 0.002) and 4.4 times (p<0.002), respectively) was also noted. The administration of pumpkin and marigold extracts reduced the amyloid β-peptide concentration in the rats' hippocampus by 54.4% (p><0.0002) and 54.4% (p><0.0002), respectively. The te>< 0.002), respectively) was also noted. The administration of pumpkin and marigold extracts reduced the amyloid β-peptide concentration in the rats' hippocampus by 54.4% (p<0.0002) and 54.4% (p><0.0002), respectively. The test-extracts had an equiva>< 0.0002) and 54.4% (p<0.0002), respectively. The test-extracts had an equivalent therapeutic efficacy with the reference drug. Conclusion On the basis of the obtained d>< 0.0002), respectively. The test-extracts had an equivalent therapeutic efficacy with the reference drug.Conclusion On the basis of the obtained data, it is possible to suggest the prospect of a further study of pumpkin and marigold extracts as the drugs of a targeted correction of cerebral hypometabolism.